EDUCATION VALUES IN GURINDAM COLLECTION OF KITAB TARBIYATUS SHIBYAN KH HABIBULLAH RAIS (NILAI-NILAI PENDIDIKAN DALAM KUMPULAN GURINDAM KITAB TARBIYATUS SHIBYAN KARYA KH. HABIBULLAH RAIS) - Rofiq, Ainur (Universitas PGRI Sumatera Barat, 2019)
The collection of gurindam in the Tarbiyatus Shibyan book written by KH Habibullah Ra’is has become a very popular learning media, especially on the island of Madura because it is a subject and textbook in educational institutions such as the madrasah diniyah and Islamic boarding schools. The value of education in the gurindam group can be a medium for forging the character of students into good characters. This research is classified as a type of literary research or library research that is qualitative in nature. The method used in this study is a qualitative method. The value of religious education in our collection of gurindam Tarbiyatus Shibyan by KH. Habibullah Ra’is is characterized by attitudes and concrete actions from the attitude of mankind to Allah by always carrying out what is commanded and away from its prohibitions, humans must fear Allah, always remember Allah, and expect the pleasure of Allah. The value of moral education contained in the Gurindam of the Tarbiyatus Shibyan book by KH. Habibullah Ra’is deals with communication between family members and in society.